Chemical Composition of Essential Oil from Leaves of Schinus molle L. Growing in Taif, KSA. Issue 1 (2nd January 2017) - Abdel-Hameed, El-Sayed S.; Bazaid, Salih A.
Abstract: Climatic and geographic conditions play an important role in the variations of chemical composition of essential oils and consequently its biological activities. The chemical constituents of essential oil from leaves of S. molle L. (Family Anacardiaceae) growing in Taif, KSA were investigated using capillary GC-MS technique. Mono- and sesquiterpenes represented by fifty compounds were identified and quantified. The total sesquiterpenes had the higher quantity (594.50 mg/100 g FWL) whereas the total monoterpenes had a lower quantity (353.69 mg/100 g FWL). α-phellandrene (211.70 mg/100 g FWL, 22.33%) was the major compound in the monoterpenes whereas δ-cadinene (57.72 mg/100 g FWL) and guaiol (55.69 mg/100 g FWL) were the major compounds in the sesquiterpenes. The special climate and geographic location of Taif governorate play an important role in the variation of chemical composition of S. molle essential oil. The S. molle essential oil showed promising anticancer activity toward the HepG2 cell line with IC50 = 16.33±0.78 that fall within the range of the American National Cancer Institute (NCI) criteria which considered the agent is promising when its IC50 < 20 μg/ml. Thus, this oil considered as promising anticancer potential after more in vitro and in vivo chemical and biological investigations. According to the above results, it is recommended for widespread cultivating this tree and its related species. All parts of the tree can be used as an important raw material for the extraction of essential oil used in traditional medicine as well as food and pharmaceutical industries.